Large Paraesophageal Schwannoma With Intense Prostate-Specific Membrane Antigen Expression on 68Ga-PSMA-PET/CT Mimicking Lymph Node Metastasis in a Patient With Prostate Cancer. (February 2019) - Ries, Martin; Khreish, Fadi; Veith, Christian; von den Hoff, Joachim; Ezziddin, Samer
Abstract : Abstract: Prostate-specific membrane antigen (PSMA)-PET/CT as an emerging modality in molecular imaging will lead to earlier detection and localization of relapse in prostate cancer but will undoubtedly also lead to false-positive findings, as it becomes clear that this new tracer is not as specific as its name would suggest. In this context, we present a case of a large PSMA-expressing schwannoma, a rare nerve sheath tumor mimicking paraesophageal lymph node metastasis in a patient with a history of prostate cancer and biochemical recurrence.